Astringency Modification of Mandilaria Wines: Vineyard and Winery Strategies - Christina Karadimou; Theodoros Gkrimpizis; Eleni Louki; Lamprini Roussi; Nikolaos Theodorou; Stefanos Koundouras; Stamatina Kallithraka (Beverages, 2025)
This paper aims to explore the impact of targeted viticultural and enological interventions on reducing the astringency of wines made solely with Mandilaria, a red Vitis Vinifera L. grape variety. Mandilaria is characterized by its high berry density, high tannin content, intense color and full body profile, all of which contribute to the distinctive enological characteristics of the wines while also pretending challenges for producers during vinification. This research aims to improve phenolic ripeness and adapt the wine produced to the requirements of the present consumers demands. In the vineyards of Paros Island, different intensities of leaf removal and modifications to pruning load were applied. Three distinct post-harvest grape dehydration techniques and two varying levels of seed removal during alcoholic fermentation were evaluated for their effectiveness in reducing astringency. Sensory analysis with a trained panel was also performed. The results demonstrate that post-harvest dehydration techniques, particularly air and sun dehydration, significantly influence the quality indicators of Mandilaria wines, enhancing the phenolic content, tannin levels and antioxidant activity, while also improving the phenolic ripeness and reducing the harsh tannic profile. Furthermore, seed removal effectively diminished astringency without affecting the wine’s structure. These findings suggest that the integration of these viticultural and enological techniques can significantly enhance the sensory attributes of Mandilaria wines, making them more appealing to modern consumers.